OCEANIC VERSES OF THE QUR’AN AND THEIR POINTERS TO TECHNOLOGICAL SOLUTIONS - Jandra, Mifedwil; Anshori, Anhar; Kholili, H. M.; Rahman, Arif (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2019)
This article focuses first on the semantic aspects, ontology, and categorization of oceanic verses as revealed and found in 42 verses in the Qur'an and then on how sea verses are selected as guidance for technological solutions. This study aims to find out the phenomenon of the ocean in the verses of the Koran by offering alternative interpretations of several problems, including; fire / energy in the ocean; two oceans that do not blend; deep darkness of the ocean; sea boundary; oceanic layers; and the abundant wealth of the sea for humanity. The study uses method of interpretation of bir rakyi or interpretation within reason using the scientific method. Modern semantic scientific methods, ontology, and the categorization of verses are used for further understanding and create a framework for further study in developing a foundation for Islamic Marine Knowledge. The results of the study indicate that the disclosure of layers in the sea water column -as mentioned in the Koran- could be a blessing for Muslims to be inspired and guided to find more discoveries and benefits of this water layer phenomenon. The findings in the analysis of these marine verses are postulated as ancient revelations to the most significant challenges of modern civilizationsuch as direct solutions to food and energy security; health & medicine; transportation and mobilization of goods; environmental management; and the birth of the new discipline of the Islamic Ocean Knowledge. There are clues in these oceanic verses about technological solutions to the existing and future humanitarian problems, which ultimately Muslims can use this as divine guidance.